2023
DOI: 10.3390/chemosensors11040237
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin-Based Chemoenzymatic Assay for Detection of Pollutants and Safety Assessment of Food Additives

Abstract: Chemoenzymatic assay systems are widely used to detect toxicants in various samples, including food and environment specimens. These methods are based on the ability of various types of toxicant to specifically inhibit/activate the functions of individual enzymes or enzyme systems. The present study examines the possibility of using the proteolytic enzyme trypsin as a specific marker to detect protease inhibitors in different samples. The study shows that trypsin activity is not affected by various heavy metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The IC 50 values for sorbic acid and potassium sorbate were calculated to be 1.6 and 12 mg/L, respectively [ 33 ]. A similar result was reported in [ 34 ], where the authors suggested that inhibition of the trypsin activity by potassium sorbate could occur due to the binding of the preservative to the enzyme in the region adjacent to the active center.…”
Section: Discussionsupporting
confidence: 86%
“…The IC 50 values for sorbic acid and potassium sorbate were calculated to be 1.6 and 12 mg/L, respectively [ 33 ]. A similar result was reported in [ 34 ], where the authors suggested that inhibition of the trypsin activity by potassium sorbate could occur due to the binding of the preservative to the enzyme in the region adjacent to the active center.…”
Section: Discussionsupporting
confidence: 86%
“…The final step may include pipetting the mixture onto the support and drying (Figure 2). This is the way to produce single-use reagents containing the preset amount of enzyme (Figure 3) [57][58][59][60]. In this form, they can be used in cuvette-based instruments (spectrophotometer, luminometer).…”
Section: Methods Of Producing Preparations Based On Enzymes Immobiliz...mentioning
confidence: 99%
“…However, the advantage of this method is that it saves on expensive enzyme preparations. The above-mentioned method of immobilizing enzymes by entrapping them in starch and gelatin hydrogels without any previous modifications was successfully used to produce stable preparations of butyrylcholinesterase (BChE), trypsin (Try), firefly luciferase (FLuc), and a bioluminescent bi-enzyme system of luminous bacteria: NAD(P)H:FMNoxidoreductase and luciferase (Red + Luc) [58][59][60].…”
Section: Methods Of Producing Preparations Based On Enzymes Immobiliz...mentioning
confidence: 99%
See 2 more Smart Citations